Implementation of Non Academic Learning for Students With Intellectual Disabilities - Fadilah, Nurul; Sabillah, Zita Andini; Nurhamidah, Azkiya; Fitriyani, Fitriyani (Education Achievement: Journal of Science and Research, 2024)
The primary goal of the learning process at SLBN Kabupaten Bekasi is to help develop the skills of students with special needs so that they do not feel different from their normal peers and can be accepted in society. This involves providing learning opportunities for children with Tunagrahita. The research conducted is a qualitative descriptive study aiming to present data in accordance with the realities observed in the field. The study involves the Vice Principal of SLBN Kabupaten Bekasi, skillful teachers, or Counseling Guidance teachers, and a mildly intellectually disabled Tunagrahita student. Data collection utilizes observation, interviews, and documentation. Observations at SLBN Kabupaten Bekasi indicate that the school implements a learning system for all students without discrimination. The guidance or teaching approach applied takes into consideration the characteristics and challenges faced by students, reflecting an effort to provide services tailored to their individual needs.